CSA dashboard - Kenya country profiles - Githu, Wanjiku; Ghosh, Aniruddha; Jaquet, Stéphanie; Maina, Wilson Nguru; Muriithi, Cyrus K; Mwongera, Caroline (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The dashboard presents the data coming from the Kenya County Climate Risk Profiles. There are 45 profiles for the 45 rural counties of Kenya. The data aims at informing decision on climate risk and the impacts of these risks on selected value chains in each county. The profiles were developed by the Alliance of Bioversity International and CIAT and the Government of Kenya with funding from the World Bank. The digitization of the profiles is supported by the AICCRA project